Assessing the impact of international remittances on Overseas Filipino Worker families' expenditure between commodity groups a panel approach - Lamasan, Anton Dominic P.
Between 2006 and 2009, overseas remittances accounted for 10.41-12.14% of GDP. Given the dependence of many Filipino families on the receipt of such remittances, it is important to look at how this phenomenon affects household spending patterns. Do remittances induce recipient families to spend more on investments like healthcare, education, and housing or should we expect such households to simply increase conspicuous consumption on recreation, tobacco, and alcoholic beverages? This paper examines this question using a panel dataset constructed from the 2006 and 2009 rounds of the merged Family Income and Expenditure Survey (FIES) and Labor Force Survey (LFS). Using a modified Working_Leser model, our findings suggest that remittance receipt lowers the household per capita expenditure share of tobacco, alcoholic beverages, and food consumed outside the home while raising the shares of consumer goods, recreation, medical care, and others. This implies that while there is a shift away from some commodity groups considered as non-essential, there is no significant change in household investment attributable to remittances aside from that of medical care.